2013
DOI: 10.1016/j.cell.2013.03.028
|View full text |Cite
|
Sign up to set email alerts
|

A Vitamin D Receptor/SMAD Genomic Circuit Gates Hepatic Fibrotic Response

Abstract: SUMMARY Liver fibrosis is a reversible wound-healing response involving TGFβ1 activation of hepatic stellate cells (HSCs). Here we show that vitamin D receptor (VDR) ligands inhibit HSC activation and abrogate liver fibrosis, while Vdr knockout mice spontaneously developed hepatic fibrosis. Mechanistically, we describe a pronounced redistribution of genome wide VDR binding sites (VDR cistrome) in HSCs elicited by a TGFβ1 pro-fibrotic insult. This TGFβ1-induced VDR cistrome overlaps extensively with SMAD3 bindi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
479
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 533 publications
(495 citation statements)
references
References 68 publications
14
479
1
1
Order By: Relevance
“…Furthermore, our findings suggested that overexpression of VDR impaired the decrease of E-cadherin and the increase of a-SMA normally observed in 4T1 cells following coculture with macrophages. This loss of epithelial markers with a concurrent increase in mesenchymal markers is the key indicator for EMT (23,24), which is regarded as a critical pathologic event in the initiation and promotion of metastasis (1). Therefore, our findings suggest that the loss of VDR is likely required for the prometastatic effect of TAMs.…”
Section: Discussionmentioning
confidence: 55%
“…Furthermore, our findings suggested that overexpression of VDR impaired the decrease of E-cadherin and the increase of a-SMA normally observed in 4T1 cells following coculture with macrophages. This loss of epithelial markers with a concurrent increase in mesenchymal markers is the key indicator for EMT (23,24), which is regarded as a critical pathologic event in the initiation and promotion of metastasis (1). Therefore, our findings suggest that the loss of VDR is likely required for the prometastatic effect of TAMs.…”
Section: Discussionmentioning
confidence: 55%
“…Recently, it has been reported that other ligands of nuclear receptors can also repress fibrosis. In particular, vitamin D receptor signaling prevents CCl4-induced liver fibrosis, inhibiting SMAD3 occupancy and SMAD-dependent transcriptional activity (56). Furthermore, vitamin D receptor agonists without hypercalcemic effects showed antifibrotic activity (57).…”
Section: Discussionmentioning
confidence: 99%
“…TGF-b signaling also cooperates with the Hippo pathway through interactions between the SMADs and TAZ/YAP (Varelas et al 2008). Finally, SMADs have been shown to actively direct the binding of other transcriptional regulators, as in the context of the TGF-b-induced liver fibrotic response in which TGF-b-induced SMAD3 directs the binding of ligand-bound nuclear vitamin D receptor (Ding et al 2013).…”
Section: Smad-interacting Transcription Factorsmentioning
confidence: 99%